Bank competition, foreign bank entry, and risk-taking behavior: Cross country evidence - Sichong Chen; Muhammad Imran Nazir; Shujahat Haider Hashmi; Ruqia Shaikh (Journal of Risk and Financial Management, 2019)
This unique study examines the interactive role of bank competition and foreign bank entry in explaining the risk-taking of banks over the globe. We used cross-country data for the banking sector from 2000 to 2016. Using the pooled regression model and Two-stage Least Squares model (2SLS with Generalized Method of Moments GMM), we document that foreign bank entry decreases the risk-taking behavior of the banks to a certain level and exhibits an inverted U-shaped relation with financial stability. Furthermore, the joint effect of bank competition and foreign bank entry brings financial fragility because host banks tend to make risky investments due to undue competition induced by foreign bank entry. We support the competition-fragility hypothesis when foreign bank entry goes beyond a certain threshold. Our results also suggest that restrictions on bank activities and capital regulation stringency reduce the level of the risk factor. We also applied various robustness tests, which further confirm our mainstream results. Our findings have policy implications for foreign investors and regulatory authorities.
Keywords: D4; G21; C23; L1; E44; 330; foreign bank entry; bank competition; H-statistics; pooled regression; dynamic panel models; risk-taking behavior